Financial sector change in the context of oil-abundance: Angola, 1991-2014 - Engebretsen, R (2018)
This thesis contributes to our understanding of the drivers of financial sector change in the particular case of resource-rich authoritarian countries. Existing studies assume that political leaders in countries characterized as resource-rich and authoritarian are disinterested in advancing financial markets. These studies moreover assume that the resource wealth that these leaders have at their disposal makes them act to the detriment of the financial sector without bearing any consequences. This thesis challenges these existing interpretations. Building on a detailed qualitative case study of financial sector change in Angola, covering the period from 1991 to 2014, the thesis argues that contrary to what prevailing theories might expect, the financial sector has been useful for maintaining Angola’s resource rich ruling coalition in a position of power. Financial sector change in the country is explained by political leaders’ need to appease supporters coupled with the latter’s ability to balance the pressure of domestic excluded factions and external actors. When political leaders are not able to satisfy their supporters, they are inclined to introduce financial sector change. Their ability to do so, however, depended on political leaders’ ability to balance the pressures exerted on them by domestic and external actors. The study contributes to the political economy of finance literature by offering a new take on how the financial sector can benefit regime survival and using this logic to explain the process of financial sector change in the setting of a resource-rich and authoritarian country. This study of Angola moreover adds to the growing scholarship seeking to nuance the assumption that leaders of resource rich authoritarian countries are autonomous from societal demands. Drawing on data collected over five months of fieldwork in Angola, the thesis also contribute empirically by being amongst the first studies to critically examine the political economy of postcolonial finance in one of Africa's largest economies.